2006
DOI: 10.1007/s00271-006-0042-z
|View full text |Cite
|
Sign up to set email alerts
|

Sprinkler irrigation scheduling of winter wheat in the North China Plain using a 20 cm standard pan

Abstract: Based on evaporation from a 20 cm diameter pan placed above the crop canopy, sprinkler irrigation scheduling of winter wheat was studied in the North China Plain (NCP) in the 2001-2004 winter wheat seasons. Results showed that pan evaporation (E pan,C ) was closely related to actual evapotranspiration (ET) measured using weighing lysimeters. The combined pan-crop coefficient (K c,pan ), the ratio of ET to E pan,C , was closely related to leaf area index (LAI ) and plant height. Data from the 2002-2003 season w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 36 publications
1
34
2
Order By: Relevance
“…The advantages of a 20 cm pan are its small size, ease of transport, low cost, and simplicity of measurement (Liu and Kang 2007). A comparison between evaporation from the 20 cm pan and reference crop evapotranspiration calculated with the FAO 56 Penman-Monteith method (Allen et al 1998) was reported by Liu and Costa (1998), Fan et al (2006) and Liu and Kang (2007). They all found that the 20 cm pan gave better predictions of reference ET (ET o ) when a locally calibrated pan coefficient was used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of a 20 cm pan are its small size, ease of transport, low cost, and simplicity of measurement (Liu and Kang 2007). A comparison between evaporation from the 20 cm pan and reference crop evapotranspiration calculated with the FAO 56 Penman-Monteith method (Allen et al 1998) was reported by Liu and Costa (1998), Fan et al (2006) and Liu and Kang (2007). They all found that the 20 cm pan gave better predictions of reference ET (ET o ) when a locally calibrated pan coefficient was used.…”
Section: Introductionmentioning
confidence: 99%
“…They all found that the 20 cm pan gave better predictions of reference ET (ET o ) when a locally calibrated pan coefficient was used. In recent years the 20 cm pan has been widely and successfully used for the estimation of ET and for irrigation scheduling (Wang et al 2002;Yuan et al 2004Yuan et al , 2006Liu and Kang 2007).…”
Section: Introductionmentioning
confidence: 99%
“…K C values feature a crop specific distinctive distribution curve throughout the growing period and are closely related to LAI development (Liu & Kang, 2007), as they mimic plant development. Each crop has three to four different development stages during its 150-day growing period: nursery (rice only), crop development, mid-season, and late-season.…”
Section: The Watergap3 Modelmentioning
confidence: 99%
“…K C values feature a crop specific distinctive distribution curve throughout the growing period and are closely related to LAI development (Liu and Kang, 2007), as they mimic plant development. For example, the barley K C increases between day 1 and 120 from 0.3 to 1.2, and then decreases until day 150 to 0.25.…”
Section: Watergap3mentioning
confidence: 99%